Challenges in Achieving Optimal Warfarin Anticoagulation Control: A Comprehensive Exploration and Proposed Holistic Approaches - Nilamsari, Wenny Putri; Hamdani, Indri Yuliani; Suprapti, Budi; Assegaf, Mochammad Yusuf; Yogiarto, Mohammad; Suharjono (Indonesian Journal of Pharmacy, 2023)
In Indonesia warfarin remains the most widely oral anticoagulation prescribed. However, the time in therapeutic range remain low in Indonesia and also in some countries in throughout the world. This study aimed to analyse the challenges of optimal warfarin control from the perspectives of healthcare professionals, patients, health system, and to propose strategies to address these challenges. This research consists of two stages. The first stage was a prospective observational study aiming to analyse the challenges and the second stage of the research was focus group discussion to propose strategies to overcome the challenges. The result of this study showed that the average of TTR was 49.4 ± 32.1, where only 37.5% patients had TTR ≥ 65%. The average dosing consistency obtained was 62.33 ± 32.42%. With regard to INR monitoring interval, almost all patient who had supraterapeutic INR had their INR monitoring interval set to 1 month after the dose adjustment. There were also identified that only 43.8% patients classified as adherent and only 39.5 % patients had good knowledge of warfarin, indicating that the level of medication adherence and knowledge was not optimal. In this study, 14.6% of patients received other drugs that potentially interacted with warfarin that cause fluctuate INR. In conclusion, this study’s results showed that there were multiple challenges for optimal warfarin control including barrier for dosing consistency, INR monitoring, patients’ adherence and knowledge, as well as drug interactions. However, there will be still room for improvement. The proposed strategy that likely will achieve optimal benefit was a holistic approach that combine multifaceted strategies to address each barrier.